Budaya Demokrasi dalam Kehidupan Masyarakat Desa di Bali - Wayan Gede Suacana (Pusat Kajian Bali Universitas Udayana, 2011)
AbstractDemocratic culture in the lives of villagers in Bali has some of the proceduralprinciples of a modern democracy. Some parameters are the rotation of power,open leadership recruitment systems, order management turnover, recognitionof appropriate manners, tolerance of differences of opinion, and accountabilityof power holders. Application of democratic culture clearly affects how desapakraman elaborates the concept of democracy as a power base andindependence. In addition, it also determines the shape and nature of relationsbetween the desa pakraman with desa dinas, this condition could be the basis ofprocedural democracy as one of the values of local wisdom in the development ofcultural tourism in Bali